THE THYMUS GLAND (THYMUS) ASPECTS IN CHILDREN (PART IV). TIMUS AND COVID-19 - Юрий Иванович Ровда (The Publishing House Medicine and Enlightenment, 2021)
At this stage in the development of immunology, it is still difficult to draw the line between the functions of the central and peripheral organs of the immune system, cell populations of the hematopoietic system, neuro-endocrine and connective tissue, which ensure the constancy of the internal environment, nonspecific defense factors (etc.). However less, time will solve this problem and there will be a possibility of complementary therapeutic and prophylactic control over the infectious process, tumor growth, autoaggression, organ and tissue transplantation, etc.This article is an attempt to get closer to understanding the main or indirect role of the thymus gland in the complex reciprocal process of interaction of the above organs and systems in countering such a viral infection as COVID-19.